Energy Transition with Variable and Intermittent Renewable Electricity Generation - Aude Pommeret; Katheline Schubert (Center for Economic Studies and ifo Institute (CESifo), 2019)
We propose one of the first dynamic models of the optimal transition from fossil fuels to renewables in electricity generation that takes into account the variability and intermittency of renewable energy as well as storage. This work sheds light on the extent to which variability and intermittency constitute a serious obstacle to energy transition and, given these constraints, the value of storage. The results of this model provide useful insight into the complexity of transitioning to a clean energy mix, as well as the role climate policy can play in facilitating both the growth of renewables and storage.
Keywords: Q42; Q54; 330